Effect of severe plastic deformation on radiation hardening of T91 ferritic-martensitic steel - Voyevodin, V.N.; Tolstolutskaya, G.D.; Karpov, S.A.; Velikodnyi, A.N.; Tikhonovsky, M.A.; Kalchenko, A.S.; Tolmachova, G.N.; Vasilenko, R.L.; Kopanets, I.E. (Вопросы атомной науки и техники, 2021)
Effect of thermomechanical treatment on radiation hardening behavior in T91 ferritic-martensitic steel was evaluated. An applying of severe plastic deformation (SPD) by the “upsetting-extrusion” method and subsequent heat treatment led to a considerable grain refinement, crushing of martensite lamellas, reduction of MX carbides size and their more uniform distribution. Nanoindentation measurements of SPD-modified steel revealed a 1.4-fold increase in the hardness relative to the initial steel. Irradiation response of modified steel was examined after 1.4 MeV Ar+ ion irradiations in the dose range of 10…45 displacements per atom (dpa) at room temperature and 460 °C. Microstructure characterization was performed by means of transmission electron microscopy (TEM). It was found that dislocation loops and nano-sized argon bubbles dominated the damage microstructure after ion irradiation. The effects of SPD-induced transformations as well as nano-bubbles formation are discussed regarding to the hardening phenomenon observed in irradiated steel. Вивчено вплив термомеханічної обробки на радіаційне зміцнення феритно-мартенситної сталі Т91. Використання інтенсивної пластичної деформації (ІПД) методом «осаджування-видавлювання» з подальшою термообробкою призвело до значного подрібнення зерна, дроблення ламелей розподіленого мартенситу, зменшення розмірів карбідів типу МХ і більш рівномірному їх розподілу. Вимірювання нанотвердості ІПД модифікованої сталі показало збільшення твердості в 1,4 рази в порівнянні з вихідною сталлю. Радіаційну стійкість модифікованої сталі досліджували після опромінення іонами Ar+ з енергією 1,4 МеВ у діапазоні доз 10…45 зсувів на атом (зна) при кімнатній температурі і 460 °C. Вивчення мікроструктури виконувалося за допомогою просвічувальної електронної мікроскопії (ПЕМ). Виявлено, що дислокаційні петлі і нанорозмірні бульбашки аргону переважають у мікроструктурі пошкоджень після іонного опромінення. Обговорюються впливи індукованих ІПД-перетворень, а також нанобульбашок аргону на зміцнення, що спостерігається в опроміненій сталі. Изучено влияние термомеханической обработки на радиационное упрочнение ферритно-мартенситной стали Т91. Использование интенсивной пластической деформации (ИПД) методом «осадки-экструзии» с последующей термообработкой привело к значительному измельчению зерна, дроблению ламелей распределенного мартенсита, уменьшению размеров карбидов типа МХ и более равномерному их распределению. Измерение нанотвердости ИПД модифицированной стали показало увеличение твердости в 1,4 раза по сравнению с исходной сталью. Радиационную стойкость модифицированной стали исследовали после облучения ионами Ar+ с энергией 1,4 МэВ в диапазоне доз 10…45 смещений на атом (сна) при комнатной температуре и 460 °C. Изучение микроструктуры выполнялось с помощью просвечивающей электронной микроскопии (ПЭМ). Обнаружено, что дислокационные петли и наноразмерные пузырьки аргона преобладают в микроструктуре повреждений после ионного облучения. Обсуждаются влияния индуцированных ИПД-превращений, а также нанопузырьков аргона на упрочнение, наблюдаемое в облученной стали.